A novel smart irrigation framework with timing allocation using solenoid valves and Arduino microcontroller - Ramakrishnaiah, Vijaya Kumar Hemapura; Lakshmappa, Harish; Gururaj, Bharathi; Muniyappa, Ramesha; Siddaramaiah, Pavan Godekere; Bylamurthy, Nagesh Hunnigere (Institute of Advanced Engineering and Science, 2024)
Irrigation in agriculture is the most common way of providing water to agricultural land or fields at normal stretches through channels and embedded platforms with the internet of things (IoT), to upgrade rural development. In this paper, the arrangement of the various types of irrigation systems and embedded platforms for agriculture was studied. The embedded platform can be designed in a suitable framework that can assist the irrigation system in growing more water-required crops. In this work, three relay switches, two solenoid valves, and one water pump source were connected to Arduino ESP32. The free version of Sinric Google Cloud was utilized significantly to control three devices namely, two solenoid valves using two relay switches and a water pump source using one relay switch. The experiment was executed in a prototype manner with timing allocation by considering two agricultural fields where water was supplied either in one field at a time and showed more prominent results to save time, replacement of manual valves, man intervention, power, and suitable quantity of water for more water-required crops namely, arecanut and coconut.